Embryonic dormancy in seeds of Bactris gasipaes Kunth (peach-palm) - Nazário,Patricia (2017)
Abstract: Bactris gasipaes is a domesticated palm whose fruits are of great importance for the Amazonian people and whose heart of palm is also receiving economic interest in other brazilian and Latin America regions. The aim of this study was verify embryonic dormancy and its correlation with first cataphyll emergence in B. gasipaes seeds collected from four plants at Manaus city and four others at Coari city, both in the Amazonas state, Brazil. After extraction and cleaning, some of the seeds (4 replications of 25 per plant) were sown in a seedbed with a sawdust and sand mixture as substrate, and embryos (4 replications of 10 per plant), after extraction, were inoculated into half strength Murashige and Skoog cultures. Were used 100 seeds and 40 embryo per treatment. Whole seed and embryo germination varied between the different source plants and locations, with the greatest difference observed for the emergence of first cataphyll from seeds in the seedbed. For the most part of variables, results of seed and embryo were positively associated, namely, as one went up the other also, and vice versa. These results suggesting that, at least in part, seed dormancy in Bactris gasipaes is associated with embryonic dormancy.